2015 IEEE International Conference on Data Science and Data Intensive Systems 2015
DOI: 10.1109/dsdis.2015.114
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Role of Topological Transitivity in Efficient Trust and Reputation System in Smart Metering Network

Abstract: Trust and reputation management represents a significant trend in tackling the security problems in computer networks. The basic idea is to let machines rate each other and then use the aggregated ratings to derive trust scores, which can assist machines in deciding whether to collaborate or not in the future tasks. Recently there are rapidly growing research literatures on trust management but these researches mainly focus on studying how to model and evaluate the trust so as to effectively detect and avoid m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Though not creating their trust model, Bello et al explored the impact of transitivity in network topology in the performance evaluation of the famous EigenTrust model [36]. They demonstrated that a network containing established transitivity connections implied that a benevolent node was quickly identified by a node, thereby reducing the average energy consumption.…”
Section: Research Areasmentioning
confidence: 99%
“…Though not creating their trust model, Bello et al explored the impact of transitivity in network topology in the performance evaluation of the famous EigenTrust model [36]. They demonstrated that a network containing established transitivity connections implied that a benevolent node was quickly identified by a node, thereby reducing the average energy consumption.…”
Section: Research Areasmentioning
confidence: 99%